In the teaching of foreign languages, the level of learning depends on the age of the students - Urishev, Omadjon Musurmonqul oglu; Urisheva, Xosiyatoy Davron qizi (Science and Education, 2023)
In the teaching of foreign languages, the level of learning largely depends on the age of the students. Language acquisition is a complex process and it is widely recognized that young learners tend to absorb new information faster than adults. Therefore, it is important to adapt the language instruction to suit the learners’ age and cognitive abilities.